Ionotropic purinergic receptor 7 (P2X7) channel structure and pharmacology provides insight regarding non-nucleotide agonism - Rua'a Al-Aqtash; Daniel M. Collier (Taylor & Francis Group, 2024)
ABSTRACTP2X7 is a member of the Ionotropic Purinergic Receptor (P2X) family. The P2X family of receptors is composed of seven (P2X1-7), ligand-gated, nonselective cation channels. Changes in P2X expression have been reported in multiple disease models. P2Xs have large complex extracellular domains that function as receptors for a variety of ligands, including endogenous and synthetic agonists and antagonists. ATP is the canonical agonist. ATP affinity ranges from nanomolar to micromolar for most P2XRs, but P2X7 has uniquely poor ATP affinity. In many physiological settings, it may be difficult to achieve the millimolar extracellular ATP concentrations needed for P2X7 channel activation; however, channel function is implicated in pain sensation, immune cell function, cardiovascular disease, cancer, and osteoporosis. Multiple high-resolution P2X7 structures have been solved in apo-, ATP-, and antagonist-bound states. P2X7 structural data reveal distinct allosteric and orthosteric antagonist-binding sites. Both allosteric and orthosteric P2X7 antagonists are well documented to inhibit ATP-evoked channel current. However, a growing body of evidence supports P2X7 activation by non-nucleotide agonists, including extracellular histone proteins and human cathelicidin-derived peptides (LL-37). Interestingly, P2X7 non-nucleotide agonism is not inhibited by allosteric antagonists, but is inhibited by orthosteric antagonists. Herein, we review P2X7 function with a focus on the efficacy of available pharmacology on P2X7 channel current activation by non-nucleotide agonists in effort to understand agonist/antagonist efficacy, and consider the impact of these data on the current understanding of P2X7 in physiology and disease given these limitations of P2X7-selective antagonists and incomplete knockout mouse models.